Urgensi Peran Fatwa DSN-MUI Dalam Mendukung Industri Asuransi Syariah - Pranoto Effendi (Pusat Riset dan Inovasi Nasional, 2025)
The insurance industry holds a vital role in the Islamic financial system by supporting risk management and contributing to the stability of the financial sector. One of the fundamental components underpinning the legitimacy and operation of sharia-compliant insurance (takaful) in Indonesia is the issuance of fatwas by the National Sharia Council – Indonesian Ulema Council (DSN-MUI). This paper aims to analyze the urgency and significance of DSN-MUI fatwas as a foundation of fiqh muamalah (Islamic commercial jurisprudence) in fostering the growth and institutional development of the sharia insurance industry in Indonesia. Using a qualitative approach with a content analysis method, this study examines each fatwa in detail by contextualizing it within the current and historical development of the sharia insurance industry. The findings reveal that there are fourteen fatwas issued by the DSN-MUI that specifically address various aspects of sharia insurance. These fatwas can be categorized into three main domains. First, fatwas that address the conceptual and systemic framework of sharia insurance. Second, fatwas that discuss the contracts used in sharia insurance operations, such as akad tabarru’, wakalah, and mudharabah. Third, fatwas that govern the types and characteristics of specific sharia insurance products.These three domains form a comprehensive and cohesive legal foundation that supports the implementation, regulation, and innovation of the sharia insurance sector in Indonesia. Furthermore, these fatwas play a strategic role in legitimizing the industry, guiding stakeholders, and ensuring the alignment of insurance practices with Islamic legal and ethical principles.